2005
DOI: 10.1021/ic050103o
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Steric and Electronic Properties of the Defect Site, Lanthanide Ionic Radii, and Solution Conditions on the Composition of Lanthanide(III) α1-P2W17O6110- Polyoxometalates

Abstract: This study identifies the principles that govern the formation and stability of Ln complexes of the (alpha(1)-P(2)W(17)O(61))(10-) isomer. The conditional stability constants for the stepwise formation equilibria, K(1cond) and K(2cond), determined by (31)P NMR spectroscopy, show that the high log K(1cond)/log K(2cond) ratio predicts the stabilization of the 1:1 Ln/ (alpha(1)-P(2)W(17)O(61))(10-) species. The value of log K(1cond) increases as the Ln series is traversed, consistent with the high charge/size req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 58 publications
4
35
0
Order By: Relevance
“…Francesconi examined the speciation of lanthanide complexes of [α 1 ‐P 2 W 17 O 61 ] 10– in depth to develop their luminescence properties. [α 1 ‐P 2 W 17 O 61 ] 10– and lanthanide ions Ln 3+ form predominantly 1:1 POM/Ln complexes, in particular, with later, smaller lanthanides 117. This behavior was further confirmed in organic solution during a collaboration of our groups 118.…”
Section: Chiral Pom Structuresmentioning
confidence: 68%
“…Francesconi examined the speciation of lanthanide complexes of [α 1 ‐P 2 W 17 O 61 ] 10– in depth to develop their luminescence properties. [α 1 ‐P 2 W 17 O 61 ] 10– and lanthanide ions Ln 3+ form predominantly 1:1 POM/Ln complexes, in particular, with later, smaller lanthanides 117. This behavior was further confirmed in organic solution during a collaboration of our groups 118.…”
Section: Chiral Pom Structuresmentioning
confidence: 68%
“…We have already shown that no leaching from the POM/Yb complex took place. Previous work indicated that the complexation constants for the Ln complexes of POMs in water are extremely high9c and are presumably higher in less polar organic solvents.…”
Section: Resultsmentioning
confidence: 99%
“…[33] We decided to follow this approach and recorded the spectra of a series of complexes {a 1 The largest chiral differentiation is obtained for {a 1 -Yb}, which may be attributable to larger paramagnetic shift of the complex. [42] Consequently, this complex was chosen for subsequent studies.…”
Section: Resultsmentioning
confidence: 99%